2004
DOI: 10.1152/ajplung.00218.2003
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide-mediated inhibition of alveolar fluid clearance in BALB/c mice after respiratory syncytial virus infection

Abstract: Respiratory syncytial virus (RSV) is the most common cause of lower respiratory tract disease in infants and children worldwide. Intranasal infection of BALB/c mice with RSV strain A2, but not ultraviolet-inactivated RSV, for 2 or 4 days reduced basal alveolar fluid clearance (AFC), a seminal function of bronchoalveolar epithelium, and caused loss of AFC sensitivity to amiloride inhibition. Reduced AFC was temporally associated with increased lung water content but was not a consequence of increased epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
94
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 47 publications
15
94
1
Order By: Relevance
“…2A, significant weight loss was observed for unimmunized animals or mice immunized either with UV-RSV or WT-BCG, as well as BCG-OVA (data not shown). These data are consistent with previous studies indicating that naive mice challenged with RSV can show significant weight loss as early as 24 h after infection (35)(36)(37). In sharp contrast, mice immunized with either BCG-N or BCG-M2 showed no significant weight loss after RSV challenge, similarly to uninfected mice (Fig.…”
Section: Resultssupporting
confidence: 93%
“…2A, significant weight loss was observed for unimmunized animals or mice immunized either with UV-RSV or WT-BCG, as well as BCG-OVA (data not shown). These data are consistent with previous studies indicating that naive mice challenged with RSV can show significant weight loss as early as 24 h after infection (35)(36)(37). In sharp contrast, mice immunized with either BCG-N or BCG-M2 showed no significant weight loss after RSV challenge, similarly to uninfected mice (Fig.…”
Section: Resultssupporting
confidence: 93%
“…It seemed that the MoA of the de novo pyrimidine as a drug target would suit more for a rapidly replicating RNA virus. Indeed, for RSV there were two reports that used the mouse model of RSV and showed that the active metabolite of leflunomide did not have an antiviral effect but did block the immuno-and lung pathology associated with the disease (50,51). However, none of these animal experiments addressed the pharmacokinetics of the drug and, most importantly, the possible toxicity associated with on-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…RSV and POPG mixtures were prepared in PBS and inoculated intranasally into mice. Aliquots of RSV stocks were inactivated by exposure to 1,800 mJ of UV radiation in a Stratalinker UV cross-linker (UVP), for the purpose of eliminating viral infectivity without significantly altering the conformation of viral proteins, or inactivating endogenous mediators, as previously described (37). UV inactivation reduced RSV infectivity by 8 log units.…”
Section: Methodsmentioning
confidence: 99%